2020
DOI: 10.1001/jama.2020.0233
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Bacterial Vaginosis in Pregnant Adolescents and Women to Prevent Preterm Delivery

Abstract: IMPORTANCE Preterm delivery results in adverse outcomes; identifying and treating bacterial vaginosis may reduce its occurrence. OBJECTIVE To update the evidence on screening and treatment of asymptomatic bacterial vaginosis in pregnancy for the US Preventive Services Task Force.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 77 publications
(322 reference statements)
1
39
0
2
Order By: Relevance
“…A recent review concluded that BV treatment has no benefit in low-risk pregnancies for women with a previous PTB the data is inconclusive. [13] The guidelines of the four countries with the most respondents are consistent with this recent data. The Dutch guideline advises BV screening and treatment in women with previous PTB.…”
Section: Discussionsupporting
confidence: 82%
“…A recent review concluded that BV treatment has no benefit in low-risk pregnancies for women with a previous PTB the data is inconclusive. [13] The guidelines of the four countries with the most respondents are consistent with this recent data. The Dutch guideline advises BV screening and treatment in women with previous PTB.…”
Section: Discussionsupporting
confidence: 82%
“…The US Preventative Task Force Services released updated recommendations in 2020 regarding screening and treatment of BV in pregnancy. After reviewing results from 13 randomized clinical trials, they recommend against treatment of asymptomatic BV in pregnancy, as treatment does not seem to decrease adverse obstetrical outcomes including PTB, low birth weight, or PPROM [170][171][172]. The benefits of treating high-risk individuals with a history of PTB is less clear [170].…”
Section: Addressing Infection: Trials Of Antibiotics To Prevent Ptbmentioning
confidence: 99%
“…En cuanto al tamizaje de mujeres embarazadas, las guías estadounidenses mencionan que no hay beneficio global en realizarlo (recomendación clase D), ya que la evidencia es insuficiente y no se ha logrado determinar si realmente tratar los casos asintomáticos disminuye el riesgo de parto pretérmino (9,14). En caso de realizarse, el método más simple consiste en un hisopado de secreción vaginal que se observa al microscopio, pero puede llegar a ser tan complejo como realizar pruebas de detección molecular bacteriana.…”
Section: Tamizajeunclassified